Empirical antimicrobial therapy for late‐onset sepsis in a neonatal unit with high prevalence of coagulase‐negative Staphylococcus - Roberta Maia de Castro Romanelli; Lêni Márcia Anchieta; Ana Carolina Bueno e Silva; Lenize Adriana de Jesus; Viviane Rosado; Wanessa Trindade Clemente (Brazilian Society of Pediatrics, 2016)
Objective: The aim of this study was to compare two different empiric treatments for late‐onset neonatal sepsis, vancomycin and oxacillin, in a neonatal intensive care unit with a high prevalence of coagulase‐negative Staphylococcus. Methods: A cross‐sectional study was conducted in an neonatal intensive care unit from 2011 to 2014. Data from the medical records of at‐risk newborns were collected daily. Infections were defined according to the National Health Surveillance Agency criteria. Data analysis was performed using an internal program. Results: There was a significant reduction in the number of Staphylococcus aureus infections (p = 0.008), without endocarditis, meningitis, or lower respiratory tract infection, as well as a reduction in the frequency of deaths related to S. aureus infection. There were no significant changes in the incidence of Gram‐negative bacterial or fungal infections. An increase in coagulase‐negative Staphylococcus infections was observed (p = 0.022). However, there was no measured increase in related morbidity and mortality. There was a reduction in the median number of days of treatment with oxacillin from 11.5 to 6 days (p < 0.001) and an increase of one day in the median number of days of treatment with vancomycin (p = 0.046). Conclusions: Modification of the empiric treatment regimen for neonatal late‐onset sepsis with use of oxacillin showed a significant reduction in S. aureus infections, as well as a reduction in the frequency of infections with major organ system involvement and mortality due to infection with this microorganism. As a result, oxacillin can be considered as an effective treatment for late‐onset sepsis, making it possible to avoid broad‐spectrum antibiotics.